Adverse childhood experiences in the children of the Avon Longitudinal Study of Parents and Children (ALSPAC) [version 1; referees: 3 approved] - Lotte C. Houtepen; Jon Heron; Matthew J. Suderman; Kate Tilling; Laura D. Howe (Wellcome Open Research, 2018)
Background: Exposure to adverse childhood experiences (ACEs) is a risk factor for poor later life health. Here, we describe the ACE variables measured in the children of the Avon Longitudinal Study of Parents and Children (ALSPAC) study, and a method used to derive summary measures and deal with missing data in them.    Methods: The ALSPAC data catalogue (59 608 variables) was searched in September 2017 for measures on adversity exposure between birth and 18 years. 6140 adversity questions were then screened for conforming to our ACE definitions and suitability for dichotomisation. This screening identified 541 questions on ten ‘classic’ ACEs (sexual, physical or emotional abuse, emotional neglect, substance abuse by the parents, parental mental illness or suicide attempt, violence between parents, parental separation, bullying and parental criminal conviction) and nine additional ACEs (bond between parent and child, satisfaction with neighbourhood, social support for the parent, social support for the child, physical illness of a parent, physical illness of the child, financial difficulties, low social class and violence between child and partner). These were used to derive a binary construct for exposure to each ACE. Finally, as cumulative measures of childhood adversity, different combinations of the 19 ACE constructs were summed to give total adversity scores. An appropriate strategy for multiple imputation was developed to deal with the complex patterns of missing data. Results: The ACE constructs and ACE-scores for exposure between birth and 16 years had prevalence estimates that were comparable to previous reports (for instance 4% sexual abuse, 18% physical abuse, 25% bullied, 32% parental separation). Conclusions: ACE constructs, derived using a pragmatic approach to handle the high dimensional ALSPAC data, can be used in future analyses on childhood adversity in ALSPAC children.